The Factor of Food in Biopolitics and National Security - S. A. Kravchenko (Vestnik MGIMO-Universiteta)
The paper examines the role of food factor in the liberal biopolitics from its birth to the present day. According to the author, the consequences of this policy of food administration are ambivalent in character. On the one hand, there are real gains in mass production of food, its delivery to the consumer, medical supervision of the implementation of its quality. However, on the other hand, the basic principles of this biopolitics - scientism, formal rationalism, pragmatism and commercialism have not allowed to solve the problems of social inequality in the access to healthy food and of illuminating the hunger. In the end of the last century the liberal biopolitics acquired globo-networked and neo-liberal character but the corresponding transition from the national to the global scale administration of food production only intensified risks and challenges of modern human nutrition. In a number of countries including Russia there appeared the problems of food security. The adopted national programs to address these challenges in a "world risk society" (U. Beck) will not solve them without fully understanding and practical implementation of the principle of the indivisibility of food security for all peoples of the world and implementation of the global food security. To achieve this, the author believes, it is necessary to abandon the "repair" of the current neo-liberal wing of biopolitics and its pragmatic and mercantilist approaches to human nutrition and pass over to a humanistic biopolitics. There offered a concrete roadmap motion to it, in particular, intending to strengthen the natural sciences and engineering for the production of food with the theoretical instruments of social sciences and humanities; to replace the outdated positivistic, scientistic postulate «knowledge - power" with the formula of ethical, humanistically oriented responsibility of scientists: "the integral knowledge of all sciences - quality food for the health of all people"; to rediscover the nature of formal rationality and its modern variations that in practice lead to the organized social irresponsibility that can be substituted by different types of value rationality, the ideology of humanism, ethics of eating healthy organic food produced in "ecologically friendly environment".